The factors of the equation are -1/3 and -4/3
Rewriting the equation -
9x² + 15x + 4 = 0
ax² + bx + c = 0
Factorizing the equation such that
12 and 3 are suitable factors for solving the given expression -
9x² + 3x + 12x+ 4 = 0
Taking common factors -
3x(3x + 1) +4 (3x + 1) = 0
(3x + 1) (3x + 4) = 0
x = -1/3, -4/3
So, the two factors of expression are -1/3 and -4/3
Checking the answers by keeping each value of x in expression
When x = (-1/3)
9x² + 15x + 4 = 0
9(-1/3)² + 15(-1/3) + 4 = 0
1 -5 +4 = 0
5 - 5 = 0
0 = 0
When x = (-4/3)
9x² + 15x + 4 = 0
9(-4/3)² + 15(-4/3) + 4 = 0
16 - 20 +4 = 0
- 4 + 4 = 0
0 = 0
Since for both values of x, Left Hand Side of equation is equal to Right Hand Side of equation, the resultant factors are correct.
Learn more about factorizing -
https://brainly.com/question/22048677
#SPJ4